2005
DOI: 10.1007/s00441-005-1127-3
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma and male factor signalling in the female reproductive tract

Abstract: In mammals, insemination results in the transmission of seminal factors that act, in the female reproductive tract, to promote sperm survival, to "condition" the female immune response to tolerate the conceptus and to organise molecular and cellular changes in the endometrium to facilitate embryo development and implantation. These events are initiated when signalling agents, including transforming growth factor-beta and other cytokines and prostaglandins secreted by seminal vesicle and prostate glands, intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
374
0
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 397 publications
(396 citation statements)
references
References 93 publications
(103 reference statements)
9
374
0
13
Order By: Relevance
“…Interestingly, the transfer of Treg as therapy against abortion is effective only very early in pregnancy, before implantation is taking place [28]. Accordingly, as demonstrated by Robertson (reviewed in [55]), TGF-b present in male seminal fluids appears to be activated in the female reproductive tract immediately after insemination. This would lead to immune activation necessary for implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the transfer of Treg as therapy against abortion is effective only very early in pregnancy, before implantation is taking place [28]. Accordingly, as demonstrated by Robertson (reviewed in [55]), TGF-b present in male seminal fluids appears to be activated in the female reproductive tract immediately after insemination. This would lead to immune activation necessary for implantation.…”
Section: Discussionmentioning
confidence: 99%
“…This would lead to immune activation necessary for implantation. This immune activation would not activate the rejection of male antigens because of the presence in seminal plasma of immunomodulatory molecules such as TGF-b [55]. It remains to be elucidated whether TGF-b secreted locally by Treg has the same function than the male TGF-b and whether in the abortion-prone combination a defective TFG-b is involved in defective or incomplete tolerance at the fetalmaternal interface.…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses have been proposed and it is most likely that, in the normal prostate, PSA assists in the fertilization process by liquefying human semen (Lilja, 2003). The role of PSA in PCa is unclear, but the proteolytic activity of PSA may also be involved in activating the transforming growth factor-signaling cascade, an important mechanism in the initiation and/or progression of PCa (Robertson, 2005). By activating transforming growth factor signaling in PCa cells, PSA may have an important function in stimulating angiogenesis and a variety of inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically studies in mice [1,2] and pigs [3] found SP to be essential for implantation, interacts with uterine epithelial cells and induces a postmating inflammatory cascade. Several inflammation-inducing proteins present in SP are transforming growth factor b, [1,4], prostaglandin E and interleukin-8 [7]. Transforming growth factor b triggers a surge in synthesis of cytokines such as granulocyte macrophage-colony stimulating factor and interleukin-6.…”
Section: Discussionmentioning
confidence: 99%
“…SP contains a variety of factors such as Transforming Growth Factor b, [1,4], prostaglandin E and interleukin-8 [7], that may trigger a cascade of events through pro-inflammatory cytokines synthesis leading to maternal endometrial immunomodulation increasing uterine receptivity. A beneficial effect of SP as an adjunctory factor to increase implantation and clinical pregnancy rates after in vitro fertilization and embryo transfer (IVF-ET) was indicated in a few clinical studies that used variable methodologies [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%